Experimental intertwinement of radial electric fields, fluctuations and transport with density in TJ-II plasmas - López-Bruna, D.; Alonso, A.; Blanco, E.; Calvo, I.; Castejón, F.; Estrada, T.; Herranz, J.; Hidalgo, C.; Krupnik, L.; Melnikov, A.; van Milligen, B.; Pedrosa, M. A.; et al. (Вопросы атомной науки и техники, 2006)
Traditionally, three transport regions have been considered in the TJ-II stellarator: the plasma core, where heat
deposition physics seems to dominate transport and therefore the radial electric field; a confinement or bulk plasma
region where collisional and, very likely, turbulent fluxes cooperate interlinked by radial electric fields and plasma
rotation; and a third region near the edge where plasma-wall interaction and magnetic topology add new phenomena.
This latter region, however, may still preserve the transport properties of the bulk region. We present our latest
experimental results on edge fluctuations based on probe data and fast camera image analysis, as well as HIBP plasma
potential and heat diffusion profiles in the bulk plasma, all of them tuned under a same experimental knob: the plasma
density, which is indication of a close intertwinement of transport, turbulence and electric fields in stellarator plasmas. Обычно в стеллараторе TJ II рассматривается перенос в трех областях: в горячей зоне, где перенос и, следовательно, радиальное электрическое поле определяются, по-видимому, механизмом вклада мощности нагрева; в зоне удержания или основной зоне плазмы, где столкновительные и турбулентные потоки связаны с радиальным электрическим полем и вращением плазмы; и в третьей периферической области, где взаимодействие плазмы со стенкой и магнитная топология добавляют новые явления в физику переноса. Однако эта последняя область еще может сохранять транспортные свойства основной области. В работе представлены последние экспериментальные данные по исследованию флуктуаций на периферии с помощью зондов и быстрой видеокамеры, а также измерения потенциала плазмы путем зондирования пучком тяжелых ионов (НIВР), и профили коэффициента теплопроводности в основной зоне. Всс эти данные регулируются одним и тем же экспериментальным параметром - плотностью плазмы. Этот факт указывает на тесную взаимосвязь переноса, турбулентности и электрических полей в плазме стелларатора. Звичайно в стелараторі TJ II розглядається перенос у трьох областях: у гарячій зоні, де перенос і, отже, радіальне електричне поле визначаються, очевидно, механізмом внеску потужності нагріву; в зоні утримання або основній зоні плазми, де зіткненні і турбулентні потоки пов'язані з радіальним електричним полем і обертанням плазми; і в третій, периферійній області, де взаємодія плазми зі стінкою і магнітна топологія додають нові явища у фізику переносу. Проте ця остання область ще може зберігати транспортні властивості основної області. Представлено останні експериментальні дані по дослідженню флуктуацій на периферії за допомогою зондів і швидкої відеокамери, а також вимірювання потенціалу плазми шляхом зондування пучком важких іонів (НIВР), і профілі коефіцієнта теплопровідності в основній зоні. Усі ці дані регулюються тим самим експериментальним параметром - густиною плазми. Цей факт указує на тісний взаємозв'язок переносу, турбулентності й електричних полів у плазмі стеларатора.